Identification of two transcription factors that work coordinately to regulate early development in Entamoeba - Daniela Lozano-Amado; Upinder Singh (mBio, 2024)
ABSTRACT The protozoan parasite Entamoeba has a life cycle that switches between infective cysts and invasive trophozoites. Encystation, a crucial process in parasite biology, is controlled by different mechanisms including transcriptional control. We identified two nuclear proteins in Entamoeba invadens, EIN_066100 and EIN_085620, that regulate parasite development by binding to a DNA motif (TCACTTTC) in the promoter regions of genes upregulated in the first 8 h of stage conversion. Overexpression of EIN_066100, a homolog of MAK16 protein, resulted in reduced amoebic proliferation without affecting encystation efficiency. Overexpression of EIN_085620, a protein with an RNA-recognition motif (RRM), led to increased encystation efficiency. Glutathione S-transferase (GST) pull down assays revealed that EIN_066100 interacts with EIN_085620 both in vivo and in vitro, and this interaction is mediated by the EIN_085620 RRM domain. By evaluating truncated proteins with deletions at either the N-terminal or C-terminal regions of EIN_066100, we elucidated the importance of its N-terminal region in proper protein localization, proliferation, encystation, and interaction with EIN_085620. Taken together, these results indicate a coordinated role of EIN_066100 and EIN_085620 in regulating Entamoeba development. This work sheds light on the molecular mechanisms in the earliest stages of Entamoeba encystation.IMPORTANCEAn important biological process in the biology of Entamoeba is stage conversion, which plays a crucial role in disease propagation, facilitating parasite survival outside the host and spreading to new hosts. Multiple mechanisms contribute to controlling the expression of amebic stage-specific genes such as epigenetic and transcriptional control. Identification of early transcriptional control regulators is crucial to understanding the initiation of the encystation cascade. We identified two nuclear proteins, EIN_066100 and EIN_085620, involved in the proliferation and developmental regulation of E. invadens. These proteins work by direct binding to each other and mediating encystation efficiency. Study of new regulators involved in Entamoeba development represents an important advance in a critical aspect of parasite biology.